SODIUM CITRATE AND POLYVINYLPYRROLIDONE CAPTURED SILVER NANOPARTICLES TRANSFER TO ORGANIC SOLVENTS - Mikelsone, J; Vembris, Aivars (Sciendo, 2024)
Silver nanoparticles (NPs) have gathered extensive attention due to their properties – chemical stability, good conductivity, catalytic activity, and antimicrobial activity. This makes NPs suitable for potential applications in the development of new technologies in the field of photonics, electronics, medicine, biochemical sensing, and imaging. Nanoprisms have local surface plasmon resonance starting from visible to near infra-red spectrum, broadening the possibilities of their applications. Ag NPs typically are synthesized in aqueous solution but the handling of NPs often requires their dispersion into nonpolar solvents and their mixing with organic compounds. Thus, nanoparticle transfer to organic media is essential for application in the field of emission enhancement due to NPs – organic semiconductor interaction. A shell changing method for NP tranfer was successfully used with a high transfer rate, but rather low stability. The previously proposed sonochemical method for NP transfer from aqueous to organic polymeric media is extended to different organic solvents. The ultrasonic method is suitable to obtain stable NPs in both organic solvent and organic solvent/organic compound solutions, and it can be stored at ambient conditions for at least several months. Transfer efficiency is suficient and NPs remain stable in an organic solvent like chlorobenzene, anisole, dichloromethane. The method has potential in NPs containing thin film preparation because sonication prevents the agglomeration of clusters. © 2024 Sciendo. All rights reserved. This is an open access article Mikelsone, J., and A. Vembris. "Sodium Citrate and Polyvinylpyrrolidone Captured Silver Nanoparticles Transfer to Organic Solvents" Latvian Journal of Physics and Technical Sciences, vol. 61, no. 1, Sciendo, 2024, pp. 23-34. https://doi.org/10.2478/lpts-2024-0003 published under the CC BY-NC-ND 4.0 licence.
The research has been funded by the Latvian Council of Science, project “Surface Plasmon Resonance Enhanced Light Amplification and Modulation in Organic Thin Films”, No. lzp-2019/1-0441. The Institute of Solid State Physics of the University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020- WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; Changes of shell; chemical synthesis; silver nanoprism; transfer to organic solvents